Proton magnetic resonance spectroscopy (1H-MRS) in studies of glaucoma: a scoping review / Liyana Musa ...[et al.] - Musa, Liyana; Sidek, Sabrilhakim; Yusof@Alias, Firdaus; Hanafiah, Mohammad; Musa, Azlan Azha; Mohd Razalli, Mazuin (Faculty of Applied Sciences, 2021)
Glaucoma is a disease that is chronic in nature and indistinctive at an early stage, leading to late detection. It has become a major public health problem and a leading cause of irreversible blindness worldwide. The proton magnetic resonance spectroscopy (1H-MRS), of late, has been utilised to evaluate metabolites concentration in the brain, especially for detecting neurodegenerative disease. Considering that glaucoma is a neurodegenerative disease, studies on the concentration of metabolites using 1H-MRS in glaucoma patients could be investigated. This scoping review aims to examine the extent, range, and nature of studies on the 1H-MRS technique in glaucoma disease. The literature search was conducted using MEDLINE, CINAHL and SCOPUS, dated from 2000 until 2019. Studies on glaucoma using 1H-MRS were considered. Any processing method used to characterise the metabolite concentration generated by the 1H-MRS protocol has also been considered. Nine full-text studies were yielded after hundreds of literature identification, screening, and eligibility assessment. The included studies sought to determine the feasibility, change, and comparability of metabolite concentrations in glaucoma patients using 1HMRS with more studies utilising single-voxel spectroscopy (SVS) technique. The chosen anatomy of interest could have been influenced by several criteria, including the association between anatomy and the research query and the volume-sizing capabilities of the 1H-MRS technique. Six (6) metabolites were significantly identified, and quantified, including N-acetyl aspartate, Creatine, Choline, Myo-Inositol, Lactate and Glutamate-Glutamine. This scoping review points out the 1H-MRS application in different types and severity of glaucoma, highlighting the information on the type of patients, the detected metabolites in the anatomy involved, the 1H-MRS technique used and the raw data decipherment processing software. Future studies are needed to validate existing glaucoma studies and to explore the potential of detecting incipient glaucoma.